HOAX AND INTOLERANCE: Implications of Social Media Reporting on the Emergence of Intolerance in Muslim Communities in Indonesia - Ibnu Azka; Ramadhanita Mustika Sari; Nurfadillah Nurfadillah (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This study discusses the impact of social media reporting on the development of disharmony in Islamic society in Indonesia. This is an interesting study because of the growing issue that the cause of the emergence of intolerant attitudes among Muslim communities in Indonesia is because they read a lot of news on social media that has elements of propaganda. One of these intolerance attitudes can be seen from the appearance of blaspheming one another, even if it's only in the comments column. This study used a qualitative method, with data collection techniques in the form of observations on news coverage on social media, and supported by data collection techniques in the form of documentation. The approach used to analyze the data that has been collected is Fairclough's critical discourse theory. This study concludes that content on social media that is indicated as a hoaks has an impact on the emergence of intolerance in Islamic society in Indonesia.